Recalculating the staff required to run a modern assisted reproductive technology laboratory. Issue 8 (2nd June 2022) - Veiga, E; Olmedo, C; Sánchez, L; Fernández, M; Mauri, A; Ferrer, E; Ortiz, N
Abstract: STUDY QUESTION: What number of staff is sufficient to perform increasingly complicated processes in today's modern ART laboratories? SUMMARY ANSWER: The adequate number of personnel required for the efficient and safe operation of modern ART laboratories needs to be calculated. WHAT IS KNOWN ALREADY: In today's modern ART laboratories, the amount of time required to perform increasingly complicated processes has more than doubled, with a downward trend in the amount of work an embryologist can do. Different workload unit values have been used to evaluate each workload task and efficiency in a particular ART laboratory, as well as to occasionally compare one laboratory with another. STUDY DESIGN, SIZE, DURATION: Seven senior embryologists working at different IVF centers, three public and four private centers, participated in this multicenter study conducted between 2019 and 2020. We prepared a survey to create a calculator for staff using the average (of three attempts) time spent in every laboratory by each embryologist of the center to perform any ART process. PARTICIPANTS/MATERIALS, SETTING, METHODS: Different laboratory processes and activities related to quality control, time spent and conventional human double witnessing were included in the survey. To calculate the number of processes that each embryologist can perform per year, an embryologist was considered to be having a full-time contract and working 7 or 8 h/day. The times included in the calculation of each task were those corresponding to the 95th percentile. For the calculations, Microsoft ® Office Excel ® Professional Plus 2019 was used. MAIN RESULTS AND THE ROLE OF CHANCE: The survey showed that the time needed per embryologist to perform the different processes necessary for a classic IVF cycle without time lapse (TL) was 8.11 h, and with TL, it was 10.27 h. The calculated time also considered the time spent in documentation handling, cycle preparation, database management and conventional human double witnessing verification. An ICSI without TL needed 8.55 h, and with TL, it needed 10.71 h. An ICSI-PGT without a TL cycle needed 11.75 h, and with TL, it needed 13.91 h. Furthermore, 1.81 h should be added for every vitrification support needed. The time needed to control more than 200 critical steps, including equipment control and culture parameters, was 30 min per day plus 3.9 min per device to control. The time spent in semen analysis (including documentation handling, cycle preparation and database management) or intrauterine insemination with a partner sperm was 2.7 h. For donor sperm, an additional hour was required for the management involved. The time required to perform a testicular biopsy and cryopreserve the sample was 4 h. Similarly, the time required to perform seminal cryopreservation was 3.7 h. LIMITATIONS, REASONS FOR CAUTION: The study was conducted considering a full-time contract embryologist working 7 or 8 h/day, 5 days a week, with days off according to the Spanish regulations. However, our findings can be adapted to foreign regulations using the developed online calculation platform. WIDER IMPLICATIONS OF THE FINDINGS: A new advanced staff calculator allows any IVF laboratory to estimate the minimum number of embryologists necessary without compromising the security or success of the results. Nevertheless, we recommend a minimum of two qualified embryologists in every laboratory, regardless of the workload. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by the Asociación para el Estudio de la Biología de la Reproducción (ASEBIR). None of the authors has any conflict of interest to declare. TRIAL REGISTRATION NUMBER: N/A.